Centrifugal Pump Design with Capacity 50.6 L/Min for Water Utilization From Steam Trap As Boiler Feed Water - Hesti Sekar Sari; Ratu Fenny Muldiani; Sri Wuryanti (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2023)
Condensate water is the result of condensing steam which has decreased in temperature and pressure due to losses from the environment. Steam trap used to separate water or dew from steam resulting from a decrease in temperature. This condensate water has a temperature of 50°C. Based on the results of condensate water testing from steam trap it has permissible criteria for boiler feed. In the existing conditions, the boiler feed water requirement is 500 liters/hour with a temperature of 25°C, while the water produced from steam trap of 230 liters/hour so that to be able to meet the needs of boiler feed water, a pump designed with a capacity of 50.6 liters/minute is needed. The purpose of this research is to design a pump to utilize steam trap water as boiler feed water. Materials are selected according to requirements and standards. Condensate water from the steam trap becomes the initial parameter for calculating Head, NPSH, Impeller Diameter, and Shaft Diameter. NPSH available must be greater than NPSH request to prevent pump cavitation, which can cause damage or loss. Based on the calculations, the NPSH req value is smaller than the NPSH available, which is 4.62 m < 11.48 m. The total head is 7.97 meters, and the number of blades is 7. The design dimensions obtained are the impeller inner diameter of 29.47 mm, outer diameter of 72.58 mm, shaft diameter of 6 mm, casing diameter of 76.215 mm.